Microneedles: A Revolutionizing Model of Drug Delivery System in Pharmaceutics with Minimal Invasion - Khudhur, Abdullah Q.; Jawad, Ali Qasim; Almajidi, Yasir Qasim; Al-hakeem, Maher Abdulrazzaq (Journal of Pharmacology and Drug Development, 2025)
One of the most interesting pharmaceutical drug delivery systems with minimally invasive technique are Microneedles. In the recent years, many researchers have concluded that Microneedles can be a leading method in the future. As a drug delivery system, Microneedles can improve drug delivery by avoiding many barriers that were linked with the conventional system, these unique properties could make Microneedles widely used. The primary mechanism for improving drug delivery to the targeted site with minimal complications is by creating micro-sized pores in the skin layer. The growing interest of Microneedles in biomedical and pharmaceutical research is obtained by easy delivery of active ingredient with low invasive technique. Vaccines, peptides, and hormones are examples of molecules delivered by Microneedles. In this review, we will discuss Microneedles efficiency as drug delivery carriers, fabrication materials, and several related patents